ANALISIS PENGGUNAAN MEDIA GOOGLE CLASSROOM DALAM PEMBELAJARAN JARAK JAUH PADA MATA PELAJARAN SEJARAH. - Lestari, Anggi Dwi; Chalimi, Ika Rahmatika; Mirzachaerulsyah, Edwin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aim to find out the usege of Google Classroom in distance learning at SMA Muhammadiyah 2 Pontianak. This method of research used a qualitative methods. The sources of data in this study was teacher of history subjects and students of class XI IIS SMA Muhammadiyah 2 Pontianak. The data collection techniques used interviews,observation techniqueand dokumentation. The data analysis used several phases that is Data Reduction, Data Display, and Verification. Triangulation techniques and triangulation of data sources are used to test the validity of the data. The results showing that(1) The planning using of Google Classroom in distance learning includes the preparation of Learning Implementation Plans, peparation of materials sourced from history books and youtube. The preparation of learning media in the form of videos about history lesson material. (2) The implementation of the using Google Classroom media in distance learning includes steps in the form of perparing lessons, managing learning, providing feedback and holding teleconferences. (3) The form of evaluation ogf history learning using Google Classroom Media in distance learning includes daily assignments and Mid Semester Assessment in the form of essay questions. (4)There are some obstacles to implementation, that is the form of less stable internet network, limited internet quota, and lack of variety in the delivery of subject matter.